SURFACE HARDENING OF THE TOOLS BY NITROOXIDATION - Karshievich, Eshkabilov Kholikul; Kholikulovich, Eshkobilov Olim (International Journal of Psychosocial Rehabilitation, 2020)
In order to increase the corrosion resistance and wear resistance as well as the resistance of cutting tools made of high-speed steels, the article presents the results of the study of the possibility of using a combined method of surface hardening, consisting in nitriding in ammonia at the first stage and oxidation of the nitride layer in water vapor at the second stage. The formation of a thin dense oxide film consisting of one magnetite and a dense nitride layer under it as well as the following zone of internal nitriding were studied on the surface to be strengthened. It is studied that the combined process at the first stage at pre-eutectoid temperature for the system "Fe-N" taking into account the temperature intervals of martensitic transformation of residual austenite and at the second stage at pre-eutectoid temperature for the system Fe-O at tempering temperature intervals allows to obtain a diffusion nitride-oxide layer with the necessary structures and properties on the surface of high-speed steels.